2016
DOI: 10.1128/iai.00278-16
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of PD-1 and LAG-3 Contributes to T-Cell Exhaustion in Anaplasma marginale-Infected Cattle

Abstract: c The CD4؉ T-cell response is central for the control of Anaplasma marginale infection in cattle. However, the infection induces a functional exhaustion of antigen-specific CD4 ؉ T cells in cattle immunized with A. marginale outer membrane proteins or purified outer membranes (OMs), which presumably facilitates the persistence of this rickettsia. In the present study, we hypothesize that T-cell exhaustion following infection is induced by the upregulation of immunoinhibitory receptors on T cells, such as progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…It is noteworthy that the blockade of the PD-1/PD-L1 pathway restored anti-mycoplasma immune functions in vitro. The results obtained in this study were consistent with those in other bovine diseases, such as bovine leukemia virus (BLV) infection, Johne's disease, and bovine anaplasmosis [15,17,18].…”
Section: Immunosuppression Via Pd-1/pd-l1 In Bovine Mycoplasmosissupporting
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that the blockade of the PD-1/PD-L1 pathway restored anti-mycoplasma immune functions in vitro. The results obtained in this study were consistent with those in other bovine diseases, such as bovine leukemia virus (BLV) infection, Johne's disease, and bovine anaplasmosis [15,17,18].…”
Section: Immunosuppression Via Pd-1/pd-l1 In Bovine Mycoplasmosissupporting
confidence: 89%
“…Previous studies on chronic bovine infections, such as bovine leukemia virus infection, Johne's disease, and bovine anaplasmosis, revealed that the upregulation of bovine PD-1 and other immunoinhibitory receptors on T cells was closely associated with the exhaustion of T-cell responses and disease progression [15][16][17][18][19][20]. Moreover, blockade of the PD-1/PD-L1 pathway reactivated T-cell functions such as proliferation and cytokine production in vitro [15,[17][18][19][20]. However, the expression of PD-1/PD-L1 and their functions in bovine mycoplasmosis have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although immune cell activity was high in brain tissue during persistent infection, this failed to eliminate all the viral particles from the infected host. Further examination of the impaired virus clearance pathway revealed the up-regulation of some genes involved in immune cell suppression, such as PDL1 and LAG3, which are considered critical markers for persistent and chronic infection [240,241]. A different study analyzed the transcriptome of kelp grouper (E. moara) immune tissues (liver, spleen and kidney) and although the expression of class I major histocompatibility complex (MHC) was significantly higher in three immune tissues of the diseased grouper, many immune related genes, including humoral immune molecules (such as antibodies), the cellular mediated cytotoxic molecules (such as perforin) and some adhesion related genes were down regulated [238].…”
Section: Host Responsementioning
confidence: 99%
“…Detecting SCC related genes in bovine genome will play important roles in prevention of mastitis incidence and those genes will be used as molecular markers to select mastitis resistant cows. CD4 and LAG-3 are powerful candidate genes in many inflammatory diseases in different species (Wang et al 2017, Okagawa et al 2016. In the present study, association of two novel SNPs in 5' and 3' flanking region of bovine CD4 and LAG-3 genes, respectively, with mastitis indicator traits was evaluated.…”
Section: Discussionmentioning
confidence: 96%